(untitled) (Docentes 2.0 Journal, 2026)
Parenting competencies are guidelines within Peru’s educational policies that guide parents in raising their children, and today, they are being undermined by various family and social problems, mainly those associated with generational change and the excessive use of social media. The purpose of this research was to analyze parenting competencies at the conceptual and operational levels from the perspectives of socio-formation, the knowledge society, and complex thinking, integrating educational and affective aspects. The research was conducted within the interpretive paradigm, using the hermeneutic method, a qualitative approach, a thematic narrative design, and a cross-sectional, documentary, and bibliographic-analytical study design. Using the eight axes of conceptual mapping, an advanced search of the scientific literature was conducted across indexed journals of empirical and systematic reviews and databases such as Google Scholar, Scopus, Web of Science, and Latindex. Keywords from the UNESCO Thesaurus and the Boolean operators AND, NOT, and OR were used. Among the main results, a conceptual construct of parenting competencies from a socio-formation perspective was proposed, linking parents and children and emphasizing autonomy, participation, and social development to contribute to the holistic development of individuals and their ethical life project. Empirical studies are suggested to evaluate the relevance of this conceptual proposal in the given context.